2021
DOI: 10.1152/advan.00239.2020
|View full text |Cite
|
Sign up to set email alerts
|

Report on the online course “Basic Concepts in Neurophysiology”: a course promoted during the COVID-19 pandemic quarantine

Abstract: “Basic Concepts in Neurophysiology” was a 3-wk online course developed during six synchronous meetings combined with asynchronous activities. We proposed an active learning course that used free online platforms to teach physiology during a period in which undergraduates were not in classrooms or taking online classes due to the COVID-19 pandemic. Herein, we report the course organization and the students’ involvement in, acceptance of, and evaluation of the course. To address the students’ perceptions about t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In a previous study, our group reported that technology improves learning outcomes in neuroscience; however, this study addressed the use of these tools (Lt, Mentimeter, among others) with undergraduate students ( 26 ). Here, we demonstrated that these resources are also helpful to promote teacher training in neuroscience since the teachers’ evaluation of the online course was positive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, our group reported that technology improves learning outcomes in neuroscience; however, this study addressed the use of these tools (Lt, Mentimeter, among others) with undergraduate students ( 26 ). Here, we demonstrated that these resources are also helpful to promote teacher training in neuroscience since the teachers’ evaluation of the online course was positive.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that the teachers did not have a preference for the online resources used, even though some of them reported some degree of difficulty with the Lt platform. However, although these technologies provide powerful tools, it is essential to highlight that they are just tools and optimization of the learning environment still depends on the teacher ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the platform offered simulated data as an alternative to actual data collection (Calderon et al, 2022). During the pandemic, educators teaching various levels of anatomy and physiology courses successfully utilized Lt (Carrazoni et al, 2021;Duszenko et al, 2022). In 2020, with the COVID-19 pandemic at its height, Australian universities had to quickly transit to online teaching (McGaughey et al, 2021) and at The University of Queensland, Lt provided the necessary support to delivery animal physiology practicals online.…”
Section: Introductionmentioning
confidence: 99%